Pemberian Hak Atas Tanah Laut: Permasalahan Dan Potensi Konflik - Tuhulele, Popy; Anwar, Arman (Fakultas Hukum Universitas Pattimura, 2024)
Introduction: The integrated management of coastal and marine areas has been regulated in Law Number 27 of 2007 in conjunction with Law Number 1 of 2014, followed up by Permen ATR/BPN 17/2016, in its implementation, it has been identified as causing problems and potential conflicts in the management of coastal areas and sea, in Ambon City and West Seram District.Purposes of the Research: This research analyzes the problems and impacts of granting rights overseas, coastal areas, and small islands in Ambon City and West Seram Regency.Methods of the Research: This study uses a normative juridical research type that is exploratory.Results of the Research: It is necessary to harmonize and structure regulations for regulating the granting of land rights in the Sea and Coastal Waters and Small Islands, taking into account the existence of indigenous/local law communities, the interests of environmental preservation, and the interests of state sovereignty. Spatial planning forums need to be activated in the regions as a means of coordination and solutions to problems of spatial use in coastal areas and small islands. The granting of marine land rights needs to be reconsidered in its implementation. Coastal areas should remain public spaces whose utilization is controlled by the state. The granting of rights to the community (customary, traditional, and local) requires strict consideration, such as compatibility with spatial planning, and the existence of hereditary mastery.